Synthesis of Plasma-Polymerized Toluene Coatings by Microwave Discharge - Elhamali, Suleiman Musa (Al-Mukhtar Journal of Sciences, 2022)
Plasma- polymerized coatings were successfully applied on aluminum alloy, AA2024, surface for corrosion protection. The plasma polymerization process was carried out by low pressure microwave plasma at room temperature. The effect of microwave plasma power on the corrosion resistance of polymer coatings was investigated using the potentiodynamic polarization technique. As the microwave plasma power increased, the relative protective efficiency increased. Polymer coatings on alloy surfaces suppressed both anodic and cathodic reactions. The increment in protective efficiency was due to a higher degree of cross-linking in the coating. These findings suggest that the toluene polymer coatings provide a considerable protection barrier for aluminum alloys.